Photonics Linear and Nonlinear Interactions of Laser Light and Matter - Menzel, Ralf.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
This book covers the fundamental properties and the description of single photons and light beams, experimentally and theoretically. It explains the essentials of linear interactions and most nonlinear interactions between light and matter in both the transparent and absorbing cases. It also provides a basic understanding of modern quantum optics and lasers, as well as the principles of nonlinear optical spectroscopy. It is self-consistent and enriched by a large number of calculated illustrations, examples, and descriptive tables. Graduate students in physics and electrical engineering, as well as other sciences, will find this book a thorough introduction to the field, while for lecturers and scientists it is a rich source of useful information and a ready-to-hand reference. The new edition has been thoroughly expanded and revised in all sections.
Topics in Photonics -- Properties and Description of Light -- Linear Interactions Between Light and Matter -- Nonlinear Interactions of Light and Matter Without Absorption -- Nonlinear Interactions of Light and Matter with Absorption -- Lasers -- Nonlinear Optical Spectroscopy.
Keywords: Physics; Laboratory medicine; Physical chemistry; Quantum optics; Lasers; Photonics; Electrical engineering; Electronics; Microelectronics; Physics; Quantum Optics; Electronics and Microelectronics, Instrumentation; Physical Chemistry; Laser Technology, Photonics; Laboratory Medicine; Electrical Engineering; Electronic books